2014
DOI: 10.1039/c4cs00144c
|View full text |Cite
|
Sign up to set email alerts
|

Models and mechanisms of Hofmeister effects in electrolyte solutions, and colloid and protein systems revisited

Abstract: Specific effects of electrolytes have posed a challenge since the 1880's. The pioneering work was that of Franz Hofmeister who studied specific salt induced protein precipitation. These effects are the rule rather the exception and are ubiquitous in chemistry and biology. Conventional electrostatic theories (Debye-Hückel, DLVO, etc.) cannot explain such effects. Over the past decades it has been recognised that additional quantum mechanical dispersion forces with associated hydration effects acting on ions are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
501
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 483 publications
(537 citation statements)
references
References 155 publications
(267 reference statements)
28
501
1
7
Order By: Relevance
“…The most important factors on the enthalpy of the hydration for salt with water are the ion radius size and the ion charge, where an ion with a smaller radius (such as chloride) has greater hydration enthalpy than an ion with a larger radius (such as iodide) [61]. The amount of hydrogen bonding was found to reduce with smaller halide anions, as suggested by previous spectroscopic experiments [62].…”
Section: Discussionsupporting
confidence: 56%
“…The most important factors on the enthalpy of the hydration for salt with water are the ion radius size and the ion charge, where an ion with a smaller radius (such as chloride) has greater hydration enthalpy than an ion with a larger radius (such as iodide) [61]. The amount of hydrogen bonding was found to reduce with smaller halide anions, as suggested by previous spectroscopic experiments [62].…”
Section: Discussionsupporting
confidence: 56%
“…As such, a further rationalization of the solubility of the gases is clearly more complicated, and it falls outside of our scope here. For details of such “specific ion effects”, the readers are referred to other articles 59, 61, 71…”
Section: Theoretical Aspects Of Water Electrolysismentioning
confidence: 99%
“…Yang, 2009), but the effect of individual ions is more complicated. SO4 2-has a higher ionic strength than Cl -with respect to proteins (Baldwin, 1996;Salis & Ninham, 2014), but it has a weaker strength than Cl -with respect to liposomes (Clarke & Lupfert, 1999;Petrache et al, 2006). In this trial, SO4 2-was shown to induce larger membrane formation (Fig.…”
Section: The Influence Of Inorganic Ions On 2d Crystallisationmentioning
confidence: 69%
“…An additional consideration for 2D crystallography is that ions can facilitate the fusion of lipid bilayers either by attracting liposomes which would otherwise electrostatically repel each other (Akashi et al, 1998;Bentz & Duzgunes, 1985;Ruso et al, 2003), or through Hofmeister ion effects where ions of inorganic salts indirectly influence the solubility of organic molecules (primarily proteins but also applicable to phospholipids) via weak interactions with bulk water molecules (Baldwin, 1996;Salis & Ninham, 2014;Z. Yang, 2009).…”
Section: Anions and Cationsmentioning
confidence: 99%
See 1 more Smart Citation